Characterizing the Human Immunodeficiency Virus Care Continuum Among Transgender Women and Cisgender Women and Men in Clinical Care: A Retrospective Time-series Analysis. (23rd April 2019) - Poteat, Tonia; Hanna, David B; Rebeiro, Peter F; Klein, Marina; Silverberg, Michael J; Eron, Joseph J; Horberg, Michael A; Kitahata, Mari M; Mathews, W C; Mattocks, Kristin; Mayor, Angel; Rich, Ashleigh J; et al.
Abstract: Background: Prior studies suggest that transgender women (TW) with human immunodeficiency virus (HIV) are less likely to be virally suppressed than cisgender women (CW) and cisgender men (CM). However, prior data are limited by small sample sizes and cross-sectional designs. We sought to characterize the HIV care continuum comparing TW to CW and CM in the United States and Canada. Methods: We analyzed annual HIV care continuum outcomes by gender status from January 2001 through December 2015 among adults (aged ≥18 years) in 15 clinical cohorts. Outcomes were retention in care and viral suppression. Results: The study population included TW (n = 396), CW (n = 14 094), and CM (n = 101 667). TW had lower proportions retained in care than CW and CM (P < .01). Estimates of retention in care were consistently lower in TW, with little change over time within each group. TW and CW had similar proportions virally suppressed over time (TW, 36% in 2001 and 80% in 2015; CW, 35% in 2001 and 83% in 2015) and were lower than CM (41% in 2001 and 87% in 2015). These differences did not reach statistical significance after adjusting for age, race, HIV risk group, and cohort. Conclusions: TW experience challenges with retention in HIV care. However, TW who are engaged in care achieve viral suppression that is comparable to that of CW and CM of similar age, race, and HIV risk group. Further research is needed to understand care engagement disparities. Abstract : Transgender women (TW) experience challenges with retention in human immunodeficiency virus (HIV) care. However, TW who are engaged in care achieve viral suppression that is comparable to that of cisgender women and cisgender men of similar age, race, and HIV risk group. Further research is needed to understand care engagement disparities.